An Analysis of Students’ Grade VII Difficulties in Learning English Subject at SMPN 242 Jakarta - Sri Narwati; Siti Rodiyah; Artipah Artipah (CV. ULIL ALBAB CORP, 2024)
This research explores a comprehensive analysis of the challenges faced by class VII students at SMPN 242 Jakarta in mastering English lessons. Using a phenomenological approach with a qualitative descriptive methodology, this research has two objectives: (1) identifying various categories of learning difficulties faced by Class VII students at SMPN 242 Jakarta in English lessons, and (2) the underlying causes of factors contributing to learning difficulties This. This research consisted of Class VII E students, with data collection carried out through interviews and documentation. The data analysis process includes data reduction, data presentation, and drawing data conclusions. The research results are as follows: (1) Various categories of learning difficulties were observed in Class VII students studying English at SMPN 242 Jakarta. These categories include Learning Disorders, characterized by reduced self-confidence; Learning Disabilities, includes individuals who face challenges in understanding learning material. This research also reveals a diverse spectrum of internal and external factors that contribute to students' learning difficulties. Internally, low interest in learning is one of the key factors, which is caused by the complexity of the subject matter and students' lack of understanding. This research highlights the variety of learning difficulties experienced by class VII students at SMPN 242 Jakarta and underscores the important role of internal and external factors in shaping the learning landscape.